Factors that influence the intention to use mobile phone caller tunes for patient reporting of adverse drug reactions: a qualitative study. (September 2019) - Appiah, Bernard; Poudyal, Anubhuti; Burdine, James N.; Asamoah-Akuoko, Lucy; Anum, David Anidaso; Kretchy, Irene Akwo; Sabblah, George; Dodoo, Alexander N.O.; McKyer, E. Lisako J.
Background: Patient reporting of adverse drug reactions (ADRs) is low in low- and middle-income countries, in part because of poor awareness to report. With the increase in mobile subscription, mobile phones can be used as a platform to disseminate information on ADRs. The aim of this study was to qualitatively assess the potential of using mobile phone caller tunes (the message or sound the caller hears before the receiver answers the call) to encourage patient reporting of ADRs. Methods: A total of 38 key informant interviews and 12 focus group discussions (57 participants in groups of 4–5) were conducted in Accra, Ghana. The transcripts were analysed using key constructs of the Technology Acceptance Model (TAM) including perceived usefulness, perceived ease of use, and behavioural intention to use caller tunes for patient reporting of ADRs. Results: Respondents mentioned lack of knowledge on reporting ADRs, and their willingness to use mobile phone caller tunes to promote patient reporting of ADRs. Many respondents pointed out how ADRs usually led to discontinuity in medication use, usually without consultation with health professionals. Caller tunes were regarded an innovative, accessible and convenient platform to disseminate information on ADRs. Most respondents intended to use caller tunes with drug safety information to promote ADR reporting, particularly to help their friends and family members. Simplicity of the message, use of songs or messages in local languages and price of downloading the caller tunes were important considerations. Conclusion: There is a need for the creation and testing of caller tunes on ADRs in Ghana to promote patient or consumer reporting of ADRs. Further studies are needed to assess factors that could influence the creation and use of caller tunes to disseminate information on drug safety.